Genotoxicity Study with Special Reference to Comet Test in the Blood Cells of Workers Exposed to Sewage Water. (23rd November 2014) - Basu, Rajlaxmi; Talapatra, Soumendra Nath; Mukhopadhyay, Aniruddha; Roy Goswami, Moumit; Ray, Siddhartha Sankar; Chakrabarti, Prantar; Ram, Shidharth Sankar; Sudarshan, Mathummal; Chakraborty, Anindita; Dasgupta, Anjan; Ghosh, Uday Chand; Chakrabarti, Sila
Abstract : Awareness among sewage workers to occupational exposure is growing slowly in many developing countries. Lead (Pb) and cadmium (Cd) are present in sewage water and workers are exposed to these metals as a result of unprotected handling. These heavy metals exposures are responsible for DNA damage and lowering blood total iron (Fe) concentration. Zinc (Zn) is an element for promoting metallothionine expression and binds the free Cd. The total suspended solids (TSS), total dissolved solids (TDS), Pb, and Cd were estimated in sewage water. The whole blood Zn and Fe concentration and Pd and Cd were also estimated. Genotoxicity as indicated by DNA damage was studied by comet assay. It was observed that there were significant differences (P < 0.001 ) of Pb and Cd concentration in blood for the sewage workers when compared with control population. DNA damage was also observed to be significantly (P < 0.001 ) higher in the exposed groups but their blood Fe concentration was significantly lower, which may be the reason for their tendency for retention of blood Cd and make them more susceptible. This study also indicated that aged workers had higher blood Zn concentrations as compared to the younger (working < 20 years) workers. This may indicate a possible adaptive response. The present study proposes that younger (working < 20 years) group is more susceptible as compared to aged group (working > 20 years).